Unravelling Maternal Behaviour in Cattle for Improved Farming Practices: A Review (Indian Journal of Animal Production and Management, 2024)
This comprehensive review explores  maternal behaviour in cattle, encompassing various  aspects such as isolation before calving, licking  behaviour, vocalizations, suckling, cross-fostering,  and weaning. The initiation of maternal behavior  involves isolation from the herd, selection of nesting  sites, and heightened activity before calving.  Licking behaviour, crucial for calf stimulation,  exhibits temporal patterns with peak intensity after  birth. Challenges in maternal bonding development  include the influence of maternal experience,  housing systems, and cross-licking, affecting calf  rejection. Suckling, a fundamental behaviour, has  distinct patterns in dairy cows. Cross-fostering and  weaning practices pose challenges, with insights  into fostering success and behavioral responses to  calf separation. Overall, understanding maternal  behaviour contributes to improved cattle  management and welfare, emphasizing the need  for proving opportunities and avenues for the  expression of maternal behaviour in modern  intensive production systems.
Keywords: maternal behaviour; cattle; hormonal regulation; licking; bonding